The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12098-009-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Kangaroo mother care in a neonatal intensive care unit (NICU) in Chandigarh, India

Abstract: KMC was found to be safe, effective and feasible method of care of LBWI even in the NICU settings. Positive attitudes were observed in mothers, families and HCW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 15 publications
10
30
2
1
Order By: Relevance
“…This was similar with Odisha, Gujarat and Maharashtra findings [15]. However, the finding was lower than 96% acceptance of KMC by Indian mothers [20], 87.1% mothers who had favourable opinion towards the practice of KMC in Ghana; and 96.6% of mothers feel positive in Cape Town [21].…”
Section: Discussionsupporting
confidence: 80%
“…This was similar with Odisha, Gujarat and Maharashtra findings [15]. However, the finding was lower than 96% acceptance of KMC by Indian mothers [20], 87.1% mothers who had favourable opinion towards the practice of KMC in Ghana; and 96.6% of mothers feel positive in Cape Town [21].…”
Section: Discussionsupporting
confidence: 80%
“…From a more applied perspective, results from the present study are consistent with clinical work showing that, in infants, breastfeeding and kangaroo care, which allow proximity and interactions between the infant and the mother, are forms of enrichment that reduce risks of respiratory instability associated mainly with prematurity (5,35,42,51). The mechanisms by which such practices benefit the infant are not well understood, but the results reported here bring us to propose that the interactions between brain stem and hypothalamic mechanisms regulating breathing, the response to stress, and secretion of sexual hormones contribute to these effects.…”
Section: Perspectivessupporting
confidence: 87%
“…16 The average weight gain of 11.27 gm/kg/day was similar to that reported by M. Anchieta et al 17 Our study demonstrated that delay in initiation of KMC was associated with prolonged NICU stay and higher rates of complications.…”
Section: Discussionsupporting
confidence: 87%